The pinballs - Byars, Betsy Cromer (New York : HarperTrophy, 1987)
Three lonely foster children learn to care about themselves and each other.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
4.9
3-6
4-6
Keywords: Foster home care -- Fiction; Friendship -- Fiction; Foster home care -- Fiction; Friendship -- Fiction